A comparison of health‐related quality of life in 5‐ and 10‐year‐old Swedish children with and without cleft lip and/or palate. Issue 4 (28th July 2016) - Sundell, Anna Lena; Törnhage, Carl‐Johan; Marcusson, Agneta
Abstract : Background: The current understanding on health‐related quality of life (HRQoL) in young Swedish children with cleft lip and/or palate (CL/P) is sparse, and therefore, research on impact of CL/P on HRQoL in children is needed. Aims: To investigate HRQoL in 5‐ and 10‐year‐old Swedish children with CL/P in comparison with non‐cleft controls. Also to analyse whether there were any differences in HRQoL between children with cleft lip (with or without cleft palate, CL ± P) and cleft palate only (CP) and/or gender differences. Design: A total of 137 children with CL/P and 305 non‐cleft controls participated. HRQoL was measured with KIDSCREEN‐52. Results: All children in the study exhibited HRQoL within or above the age‐matched reference interval of the method with similar results in both groups; however, in the dimension 'social support and peers', the 10‐year‐old children with CL/P perceived lower HRQoL than the non‐cleft controls, but it did not reach statistical significance. Type of cleft or gender did not influence HRQoL. Conclusions: Both 5‐ and 10‐year‐old Swedish children with CL/P had HRQoL in the normal reference interval. Their general life situations were well adjusted to their clefts, but the older children with CL/P felt more excluded and less supported by peers.